2011
DOI: 10.4269/ajtmh.2011.10-0651
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Parasite Load and Improved Cognitive Outcomes Caused by Deworming and Consumption of Multi-Micronutrient Fortified Biscuits in Rural Vietnamese Schoolchildren

Abstract: Abstract. Micronutrient deficiencies are associated with impaired growth and cognitive function. A school-based fortification program might benefit schoolchildren but a high prevalence of parasite infestation might affect effectiveness. A randomized, double-blind, placebo-controlled 2 × 2 factorial trial was conducted to assess the efficacy of multimicronutrient fortified biscuits with or without de-worming on growth, cognitive function, and parasite load in Vietnamese schoolchildren. Schoolchildren (n = 510),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…Iron deficient children first enrolled in school were disadvantaged in terms of aptitudes, and this disappeared once they become iron-replete through supplementation [40]. Similar findings showed that multiple micronutrient fortified food was effective in improving micronutrient status and cognition [41,42], and vitamin and mineral deficiencies limit the child's optimal ability in cognition and intelligence [43]. In contrast, micronutrient supplementation during preschool years had no effect on aspects of intellectual, executive and motor function at 7-9 years old, suggesting no long-term developmental benefit during 12-35 months of age [44].…”
Section: School Performance Of Study Childrensupporting
confidence: 55%
“…Iron deficient children first enrolled in school were disadvantaged in terms of aptitudes, and this disappeared once they become iron-replete through supplementation [40]. Similar findings showed that multiple micronutrient fortified food was effective in improving micronutrient status and cognition [41,42], and vitamin and mineral deficiencies limit the child's optimal ability in cognition and intelligence [43]. In contrast, micronutrient supplementation during preschool years had no effect on aspects of intellectual, executive and motor function at 7-9 years old, suggesting no long-term developmental benefit during 12-35 months of age [44].…”
Section: School Performance Of Study Childrensupporting
confidence: 55%
“…7 Only for Ascaris, significantly lower egg counts were observed after consumption of fortified biscuits combined with albendazole treatment, compared with albendazole alone. 33 Hemoglobin concentrations were lower in Trichuris, hookworm, and in children infected with multiple STH species than in those uninfected. Surprisingly, these infections were not associated with ferritin concentrations.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies did not report sufficient data to estimate the mean difference between treatment and control groups at each follow-up (Pollitt, Hathirat, Kotchabhakdi, Missell, & Valyasevi, 1989;Sungthong, Mo-suwan, Chongsuvivtwong, & Geater, 2004;Whaley et al, 2003), in one case because statistically nonsignificant results were not reported in the paper (Nga et al, 2011). In other cases, I could not convert mean differences (or a regression coefficient estimating a similar parameter) to effect sizes, given the lack of data on the standard deviation of the outcome variable (Adelman, Alderman, Gilligan, & Lehrer, 2008;Kazianga, de Walque, & Alderman, 2012;Pandey, Goyal, & Sundararaman, 2009;Vazir, Nagalla, Thangiah, Kamasamudram, & Bhattiprolu, 2006).…”
Section: Criteria For Study Inclusion and Exclusionmentioning
confidence: 99%